Effect of gamma irradiation on shelf life and quality of indigenous chicken meat: Irradiation on chicken meat - Islam, Anisul; Sadakuzzaman, Md; Hossain, Md Anwar; Hossain, Md Mujaffar; Hashem, Md Abul (Journal of the Bangladesh Agricultural University, 2019)
The experiment was conducted on fresh indigenous chicken meat treated with 0 (non-irradiated), 1, 2 and 3 kGy 60Co gamma irradiation and stored for 0, 30 and 60 days at -20ºC to investigate the effects on proximate components, sensory attributes, and physicochemical, biochemical and microbial changes in meat quality. Data were analyzed under 4x3 factor CRD design of experiment in GLM procedure of SAS statistical package. The results showed that irradiation groups had significantly (p<0.05) higher color and tenderness of meat compared to that of non-irradiated group. The 2 kGy group showed significantly (p<0.05) higher Dry matter (DM) and Ether extract (EE) whereas the cooking loss, Free fatty acid (FFA), Peroxide value (PV), and Thiobarbituric acid reactive substances (TBARS) levels were higher in 3 kGy irradiated group. With the advancement of storage periods pH significantly (p<0.05) decreased. The 2 kGy irradiation group showed significantly (p<0.05) lower numbers of Total viable count (TVC), Total coliform count (TCC), Total yeast and mold count (TYMC) compared to non-irradiated group. From this study, it may be concluded that the 2 kGy irradiated group had positive effects on sensory evaluation, biochemical and microbial qualities of indigenous chicken meat to increase the shelf life and the quality of indigenous chicken meat. <!–StartFragment –> J Bangladesh Agril Univ 17(4): 560–566, 2019